Prospective randomised controlled trial on the effect of videos on the cooperativeness of children undergoing MRI and their requirement for general anaesthesia. Issue 10 (October 2018) - Ong, Y.Z.; Saffari, S.E.; Tang, P.H.
Abstract : Aim: To assess the effectiveness of pre-scan videos on the percentage of children requiring general anaesthesia (GA), having repeated magnetic resonance imaging (MRI) sequences due to motion, and having confidence in keeping still for at least 30 minutes during their MRI examinations. Materials and methods: In this institution review board-approved prospective study, 786 children between 3 to 21 years old scheduled for MRI were randomised into control, regular cartoon video only, and interactive cum regular cartoon video groups. Children were surveyed before and after the videos for the duration that the child was confident in keeping still. The percentage of children who required GA, who required at least one repeated MRI sequence, and confident in keeping still for at least 30 minutes in each group were compared. Results: The mean age of the children was 11.64±3.68 years. There was no difference in GA requirement across the three groups. Compared to the control group, the regular video group had 13% ( p= 0.005) reduction in requirement for at least one repeat MRI sequence with 19.6% ( p< 0.001) reduction in the combined videos group. Children confident in keeping still for at least 30 minutes increased by 21% ( p< 0.001) in the regular video group and 32.1% ( p< 0.001) in the combined videos group. Conclusion: Watching videos before the MRI examination improved the confidence of children in keeping still during the MRI and they moved less during the MRI, with a significant reduction in the requirement for repeated MRI sequences. Highlights: Watching videos before scans resulted in reduction in the requirement for repeated imaging. Confidence of children in staying still for scans improved after watching pre-scan videos. Addition of interactive video has a greater effect when compared to regular cartoon video alone.